Analysis of the multiplicity of steady-state profiles of two tubular reactor models. (9th June 2018) - Dochain, D.
Highlights: This paper concentrates on the analysis of tubular reactor models. Two models are considered: the non isothermal tubular reactor model and a biochemical reactor model. Mathematical analysis is performed and applied to both case studies. It is shown that multiple equilibrium profiles can be exhibited if the diffusion coefficients are large enough. Abstract: This paper deals with the analysis of two tubular reactor models, the non-isothermal tubular reactor model and a biochemical reactor model. It is mathematically shown in particular that multiple equilibrium profiles can be exhibited if the diffusion coefficients are large enough by considering regular perturbation arguments.